Interconnection of the immune system and the intensity of the oxidative processes under conditions of prolonged exposure to small doses of radiation - Sokolenko, V. L.; Sokolenko, S. V.; Sheiko, V. I.; Kovalenko, O. V. (Regulatory Mechanisms in Biosystems, 2018)
This research studied the interrelationship between the immune and oxidative-antioxidant systems in a group of individuals who had lived for a long time in areas contaminated with radionuclides after the Chernobyl catastrophe and as a result experienced prolonged exposure to small doses of ionizing radiation. We have examined a group of 100 students aged 18–24, where 50 of them formed the control group and the remaining 50 belonged to the experimental group as they arrived from the territories of enhanced radioecological control (IV radiation zone, density of soil contamination by isotope 137Cs 3.7 x 104 – 18.5 x 104 Bq/m2). Here we determined the level of cortisol, leukocytes and their populations, the levels of lymphocyte subpopulations with phenotypes CD3+, CD5+, CD4+, CD8+, CD16+, CD72+, immunoregulatory index CD4+/CD8+, indicators of phagocytic activity of neutrophils and monocytes, IgG (H), IgM (H), IgA (H), malondialdehyde (MDA), ceruloplasmin (CP), transferrin (Tr), sulfhydryl (SH); and also calculated the oxidative stress index (OSI). We performed the analysis twice: in the absence/presence of additional emotional stress such as an examination session. The studies showed an increase in the oxidative stress index in the group examined from the experimental cluster, especially in terms of emotional stress. At the same time, the neutrophil level increased, but phagocytic activity of neutrophils and monocytes, the relative and absolute number of lymphocytes with phenotypes CD3+, CD5+, CD4+, CD4+/CD8+, and IgG levels decreased. Consequently we revealed the negative correlation between the indexes of oxidative stress in the group of examined (the oxidative stress index (ISO)/the level of malonic dialdehyde (MDA)) and the parameters of phagocytic activity of monocytes, the immunoregulatory index CD4+/CD8+, and the number of lymphocytes with the CD16+ phenotype. In this study we demonstrated the decrease in the participation of ceruloplasmin (CP) as an important antioxidant factor in maintaining the immune homeostasis of the group examined from radiation-contaminated areas compared with control group. The evidence of this is the lack of reliable correlation between ceruloplasmin level and immune system parameters. Moreover we found that radiation-induced intensification of oxidative processes in the experimental group grew in conditions of additional stresses of an emotional nature. Besides, it was accompanied by a significant correlation in the level of oxidative stress and phagocytic activity parameters. Reducing phagocytic activity and the CD4+/CD8+ index on the background of oxidative stress increase can be considered as a sign of immune system ageing, while a decrease in the number of lymphocytes with the CD16+ phenotype is a sign of antitumor defense inhibition. Thus, we draw the conclusion that the inhabitants of the territories of strengthened radioecological control, undergoing exposure to small doses of ionizing radiation from birth, show a significant imbalance of redox homeostasis, which creates the preconditions for immunoreactivity pathology development at the level of both innate and acquired immunity.